Penerapan Metode Bernyanyi dalam Meningkatkan Penguasaan Mufradat pada Anak Usia 5-6 Tahun: Implementation of Singing Methods in Improving Vocabulary Mastery in Children Aged 5-6 Years - Lubis, Nur Asiah; Munadia, Khairani; Hasibuan, Indah Khairani; Lubis, Hilda Zahra (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Mastery of vocabulary is a crucial element in learning Arabic, particularly for young children. However, the main challenge in this process is making the learning experience both engaging and effective, in line with the developmental characteristics of 5-6-year-old children. This study aims to examine the use of the singing method as a strategy to enhance vocabulary mastery in early childhood. The research adopts a qualitative-descriptive approach, gathering data through observation, interviews, and documentation. The findings reveal that the singing method successfully creates a fun learning environment, boosts children's motivation, and helps them easily remember and acquire Arabic vocabulary. The chosen songs feature simple vocabulary that aligns with children's everyday lives, accompanied by movements to reinforce understanding and encourage active participation. The implementation of this method also supports the development of children's cognitive, emotional, and motor skills. Therefore, the singing method has proven to be an effective and innovative approach in teaching Arabic to 5-6-year-old children.